REAKTUALISASI TEOLOGI ASY’ARIYAH DAN KONTRIBUSINYA TERHADAP PENGUATAN MODERASI BERAGAMA DI INDONESIA (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2024)
This study aims to examine the characteristics of the moderate method of the Ash'arite school of thought and to analyze its contribution to strengthening religious moderation in Indonesia. This research employs a library research method with a descriptive analytical-critical approach. The researcher combines an inductive approach to trace the meaning of moderation according to Ash'arism and a deductive approach to draw conclusions on both universal and particular issues related to this concept. The findings reveal four dimensions of Ash'arism's contribution to religious moderation. First, from an epistemological perspective, Ash'arism positions reason as a servant and reinforcer of revelation, so that moderation is achieved through rigorous reasoning rather than through unsubstantiated compromise. Second, from a historical-sociological perspective, Ash'arite theology has shaped the religious character of traditional ulama in the Nusantara through the transmission of Aswaja scholarship in Islamic boarding schools, thereby giving Indonesian Islam a moderate character that is accommodating toward local traditions. Third, from a constructive perspective, the structure of Ash'arite theology aligns with the four indicators of religious moderation established by the Ministry of Religious Affairs. Fourth, in terms of preventing radicalism, Ash'arite theology can be employed to refute the theological claims of radical groups that excommunicate (takfir) others over differences in interpretation, while also explaining human moral responsibility without succumbing to fatalism that justifies violence.
Keywords: Ash'arite theology; Indonesian Islam; radicalism; religious moderation; wasathiyah.